Financial and Insurance Formulas - Cipra, Tomas; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2010)
This survey contains more than 3,000 formulas and methods from the field of finance and insurance mathematics (as well as related formulas in mathematics, probability theory, statistics, econometrics, index numbers, demography, stochastic processes and time series). The formulas are mostly applicable in financial and actuarial practice. Their mathematical level ranges from simple ones based on arithmetic to very sophisticated matters of higher mathematics (e. g. stochastic calculus), but they are usually presented in the form most frequently used in applications. Explanations and references to related parts of the survey are given so that one can easily browse and look them up in the text; the detailed Index is also helpful for this purpose. The survey will be of benefit for students, researchers and practitioners in finance and insurance.
Financial Formulas -- Simple Interest and Discount -- Compound Interest and Discount -- Continuous Interest and Discount -- Classical Analysis of Interest Rates -- Systems of Cash Flows -- Annuities -- Depreciation -- Financial Instruments -- Derivative Securities -- Utility Theory -- Rate of Return and Financial Risk -- Portfolio Analysis and CAPM Model -- Arbitrage Theory -- Financial Stochastic Analysis -- Insurance Formulas -- Insurance Classification -- Actuarial Demography -- Classical Life Insurance -- Modern Approaches to Life Insurance -- Pension Insurance -- Classical Non-Life Insurance -- Risk Theory in Insurance -- Health Insurance -- Reinsurance -- Formulas of Related Disciplines -- Mathematical Compendium -- Probability Theory -- Descriptive and Mathematical Statistics -- Econometrics -- Index Numbers -- Stochastic Processes -- Statistical Analysis of Time Series.
Keywords: Statistics; Economics -- Statistics; Finance; Statistics; Statistics for Business/Economics/Mathematical Finance/Insurance.; Financial Economics; Finance/Investment/Banking.